2003
DOI: 10.1128/iai.71.1.126-131.2003
|View full text |Cite
|
Sign up to set email alerts
|

Multigenic Control of Disease Severity after VirulentMycobacterium tuberculosisInfection in Mice

Abstract: Following challenge with virulent Mycobacterium tuberculosis, mice of the I/St inbred strain exhibit shorter survival time, more rapid body weight loss, higher mycobacterial loads in organs, and more severe lung histopathology than mice of the A/Sn strain. We previously performed a genome-wide scan for quantitative trait loci (QTLs) that control the severity of M. tuberculosis-triggered disease in [(A/Sn ؋ I/St) F1 ؋ I/St] backcross-1 (BC1) mice and described several QTLs that are significantly or suggestively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
5

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 29 publications
2
58
0
5
Order By: Relevance
“…This genomic region has been associated with susceptibility to various models of pulmonary infection including Chlamydia pneumoniae 58,59 and Mycobacterium tuberculosis. 60,61 One previous report of female H-2 congenic C57BL/10 strains bearing the H-2 k/k haplotype also demonstrated an increased cryptococcal burden in the liver 39 days following infection. 12,16 In the current study, segregation of the H-2 k/k (CBA/J) and C57BL/6J (H-2 b/b ) haplotypes was observed in our CBAB6F2 intercross population and the peak LOD score positions of the Cnes2 and Cnes3 lie proximal and distal to the H-2 region of chromosome 17, respectively.…”
Section: Genetic Control Of Cryptococcal Pneumoniamentioning
confidence: 97%
“…This genomic region has been associated with susceptibility to various models of pulmonary infection including Chlamydia pneumoniae 58,59 and Mycobacterium tuberculosis. 60,61 One previous report of female H-2 congenic C57BL/10 strains bearing the H-2 k/k haplotype also demonstrated an increased cryptococcal burden in the liver 39 days following infection. 12,16 In the current study, segregation of the H-2 k/k (CBA/J) and C57BL/6J (H-2 b/b ) haplotypes was observed in our CBAB6F2 intercross population and the peak LOD score positions of the Cnes2 and Cnes3 lie proximal and distal to the H-2 region of chromosome 17, respectively.…”
Section: Genetic Control Of Cryptococcal Pneumoniamentioning
confidence: 97%
“…17 QTL detected herein overlaps the major histocompatibility locus, a region that contains many genes regulating early (innate) and late phase (acquired immunity) of host response to infection with mycobacteria including M. bovis (BCG) (herein), and M. tuberculosis. 23,24 The effect of Chr. 17 on host response to M. tuberculosis has recently been attributed to a functional polymorphism in the tumor necrosis factor-a gene, 25 suggesting a possible modifying effect of this pleitropic proinflammatory cytokine on Nramp1-mediated resistance.…”
mentioning
confidence: 99%
“…Association of tuberculosis susceptibility with MHC polymorphisms have been previously reported both in humans 30 and in a mouse model of infection. 31,32 In mice, different alleles at specific H-2 loci affected survival after i.v. infection with virulent MTB, the level of delayed type hypersensitivity (DTH), T cell proliferative response to mycobacterial antigens, and efficacy of antituberculosis vaccination with live attenuated Mycobacterium bovis (BCG), 31 production of IFN-g by mycobacteria-specific T cells, 33,34 as well as production of mycobacteria-specific antibodies.…”
Section: Chromosome 17 Locusmentioning
confidence: 99%